Discrimination of autochthonous pig breeds from meat and fat samples by FT-NIR spectra - S. Parrini; C. Dadousis; F. Sirtori; M.C. Fabbri; M. Čandek-Potokar; J.M. Garcia-Casco; B. Lebret; R. Nieto; C. Aquilani; R. Bozzi (Biosystems Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

City divided: Unveiling family ties and genetic structuring of coyotes in Seattle - Samantha E. S. Kreling; Ellen M. Reese; Olivia M. Cavalluzzi; Natalee B. Bozzi; Riley Messinger; Christopher J. Schell; Robert A. Long; Laura R. Prugh (Molecular Ecology, 2024)
Linear barriers pose significant challenges for wildlife gene flow, impacting species persistence, adaptation, and evolution. While numerous studies have examined the effects of linear barriers (e.g., fences and roadways) on partitioning urban and non‐urban areas, understanding their influence on gene flow within cities remains limited. Here, we investigated the impact of linear barriers on coyote ( Canis latrans ) population structure in Seattle, Washington, where major barriers (i.e., interstate highways and bodies of water) divide the city into distinct quadrants. Just under 1000 scats were collected to obtain genetic data between January 2021 and December 2022, allowing us to identify 73 individual coyotes. Notably, private allele analysis underscored limited interbreeding among quadrants. When comparing one quadrant to each other, there were up to 16 private alleles within a single quadrant, representing nearly 22% of the population allelic diversity. Our analysis revealed weak isolation by distance, and despite being a highly mobile species, genetic structuring was apparent between quadrants even with extremely short geographic distance between individual coyotes, implying that Interstate 5 and the Ship Canal act as major barriers. This study uses coyotes as a model species for understanding urban gene flow and its consequences in cities, a crucial component for bolstering conservation of rarer species and developing wildlife friendly cities.

Effects of AZT on cellular iron homeostasis - Argante Bozzi; Fabrizia Brisdelli; Anna M. D'Alessandro; Gabriele D'Andrea; Anna R. Lizzi; Andrea C. Rinaldi; Arduino Oratore (BioMetals, 2004)